The Impact of the Deindustrialization Process on the Development of Tourist Activities at the Level of the Municipality of Orsova (Annals of the University of Bucharest. Geography Series, 2025)
After 1990, rapid deindustrialization generated economic difficulties and a negative demographic evolution that was more strongly felt at the level of small towns in Romania. The purpose of the work is to analyze the effects generated by the deindustrialization process at the level of the municipality of Orșova in demographic and economic terms. Special attention was paid to the impact generated on the development of tourism as a result of the fact that Orşova presents an extraordinary tourist potential. In order to highlight these changes, the analysis was focused on establishing the importance and implications of the population structure (in this case the share of the young and adult population) and economic activities (especially tourism) on the local economy. The authors used a series of indicators (economic, demographic and tourist), based on which they tried to determine the degree of adaptability of the locality to the changes that occurred in the context of deindustrialization, as well as the impact produced on tourist activities.
Keywords: deindustrialization; workforce; tourism potential; transit tourism; wetland tourism; the Danube Gorge